2000
DOI: 10.1089/104454900314654
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of L-Plastin Gene by Testosterone in Breast and Prostate Cancer Cells: Identification of Three Cooperative Androgen Receptor-Binding Sequences

Abstract: L-Plastin is normally a leukocyte-specific actin-binding protein; it is also expressed in the majority of human cancer cell lines that are derived from many types of solid tumors. We have previously reported the isolation of the L-plastin gene promoter, in which we identified several potential steroid receptor-binding sequences. We now obtained evidence that L-plastin gene expression was positively regulated by testosterone in androgen receptor (AR)-positive prostate and breast cancer cells. DNase I footprint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…LCP1 is up-regulated in prostate cancer (Lin et al, 2000) and has been suggested to be a potential marker for metastasis in colorectal cancer (Otsuka et al, 2001). Bladder cancer tissue microarray analysis also indicates that LCP1 expression is significantly correlated with tumor grade (Harris et al, 2005(Harris et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…LCP1 is up-regulated in prostate cancer (Lin et al, 2000) and has been suggested to be a potential marker for metastasis in colorectal cancer (Otsuka et al, 2001). Bladder cancer tissue microarray analysis also indicates that LCP1 expression is significantly correlated with tumor grade (Harris et al, 2005(Harris et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Among these are several proteins potentially implicated in breast cancer such as L-plastin, STAT1, haptoglobin, and thymidine phosphorylase. 5,7,14,29 Proteins that are known to be involved in the regulation of the cytoskeleton are also prominent in this list. These include L-plastin, moesin, gelsolin, and talin.…”
Section: Size-resolved Differential Profiling Of Tumor Versus Clinicamentioning
confidence: 99%
“…42 The presence of PLS3 could possibly interfere with that function. Conversely, aberrant expression of LCP1 has been reported in many cancers, including breast, prostate, 43 and colon cancer, 44 tissues that normally express PLS3, suggesting that coexpression may not be an uncommon feature of malignant cells.…”
Section: Significance Of the Selected Genesmentioning
confidence: 99%